Evaluate 6 + 9÷3*6

Question

Asked 1/4/2013 8:51:21 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

dokidoki|Points 522|

debnjerry|Points 42369|

Expert answered|jeifunk|Points 8280|

Question

Asked 1/4/2013 8:51:21 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Solve |2x + 5|

Question

Expert Answered

Updated 7/21/2014 4:20:25 PM

2 Answers/Comments

|2x + 5| < 4;

2x + 5 < 4;

2x < 4 - 5;

2x < -1;

x < -1/2

2x + 5 < -4;

2x < -4 - 5;

2x < -9;

x < -9/2

-9/2 < x < -1/2

2x + 5 < 4;

2x < 4 - 5;

2x < -1;

x < -1/2

2x + 5 < -4;

2x < -4 - 5;

2x < -9;

x < -9/2

-9/2 < x < -1/2

Added 7/21/2014 4:19:36 PM

This answer has been confirmed as correct and helpful.

6 + 9 ÷ 3 · 6

= 6 + 3 · 6

= 6 + 18

= 24

= 6 + 3 · 6

= 6 + 18

= 24

Added 7/21/2014 4:20:25 PM

This answer has been confirmed as correct and helpful.

Perform the indicated operation.
(6x^2+4x-12)-(3x^2+9x-8)
User: Solve -5 + 4x = 29 User: Evaluate |8| + |-3| - 7(-5)
**Weegy:** The answer is
6(-3)-|-5|+|3|=-20 **User:** If f(x) = 3x^2+1 find f(6) **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! **User:** 2a^2 (More)

Question

Updated 7/21/2014 4:15:33 PM

4 Answers/Comments

(6x^2 + 4x - 12) - (3x^2 + 9x - 8)

= (6x^2 + 4x - 12) + (-3x^2 - 9x + 8)

= 3x^2 - 5x - 4

= (6x^2 + 4x - 12) + (-3x^2 - 9x + 8)

= 3x^2 - 5x - 4

Added 7/21/2014 4:11:49 PM

This answer has been confirmed as correct and helpful.

-5 + 4x = 29;

4x = 29 + 5;

4x = 34;

x = 34/4;

x = 17/2

4x = 29 + 5;

4x = 34;

x = 34/4;

x = 17/2

Added 7/21/2014 4:12:34 PM

This answer has been confirmed as correct and helpful.

|8| + |-3| - 7(-5)

= 8 + 3 + 35

= 11 + 35

= 46

= 8 + 3 + 35

= 11 + 35

= 46

Added 7/21/2014 4:14:13 PM

This answer has been confirmed as correct and helpful.

f(x) = 3x^2+1, f(6)

f(6) = 3(6)^2 + 1;

f(6) = 3(36) + 1;

f(6) = 108 + 1;

f(6) = 109

f(6) = 3(6)^2 + 1;

f(6) = 3(36) + 1;

f(6) = 108 + 1;

f(6) = 109

Added 7/21/2014 4:15:33 PM

This answer has been confirmed as correct and helpful.

35,112,005

questions answered

There are no comments.